Poisonous Atmospheres: Ventilation and the late Nineteenth Century Building - Stephens, John (Department of Architectural Design Science, University of Sydney, 2003)
The desire for healthy buildings and inhabitants in the late nineteenth and early twentieth century was of prime concern for hygienists, sanitary engineers, architects and regulatory officials alike. To protect inhabitants a range of technological and operational strategies were employed to prevent the air in rooms becoming foul and contaminated. At the root of this concern and resulting technology were particular concepts and theories regarding the mechanisms by which disease spread. Foul air, whether from dangerous decomposing organic matter or from the fetid breath of ordinary individuals needed dilution and deodorisation – best managed with good ventilation. Using the situation in late nineteenth century Britain and its colony in Western Australia as a case study this paper explores the way that ventilation technology at its simplest level was informed by concepts of health and disease.